2003
DOI: 10.4049/jimmunol.170.1.294
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of CD58 or CD48 with Intercellular Adhesion Molecule 1 on Target Cells Enhances Adhesion of Resting NK Cells

Abstract: The β2 integrin LFA-1 (CD11a/CD18) mediates adhesion of lymphocytes to cells expressing ICAM. The strength of this adhesion is regulated by different signals delivered by cytokines and chemokines, and by the TCR in the case of T cells. To determine the receptor-ligand interactions required for adhesion of resting NK cells, Drosophila cells expressing different combinations of ligands of human NK cell receptors were generated. Expression of ICAM-1 alone was sufficient for an adhesion of resting NK cells that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 24 publications
3
110
0
1
Order By: Relevance
“…After isolation, cells were cultured under the indicated conditions for migration, conjugation (65)(66)(67), lentivirus transfection, and viability assays as described.…”
Section: Methodsmentioning
confidence: 99%
“…After isolation, cells were cultured under the indicated conditions for migration, conjugation (65)(66)(67), lentivirus transfection, and viability assays as described.…”
Section: Methodsmentioning
confidence: 99%
“…The b2-integrin LFA-1 plays a pivotal role in NK-cell conjugate formation. Engagement of its ligand ICAM-1 is sufficient for the formation of stable effector-target conjugates [4]. Moreover, LFA-1 signals are important for granule polarization in NK cells [5].…”
mentioning
confidence: 99%
“…In fact, resting human ex vivo NK cells appear to require engagement of at least two independent receptors to become activated (37). These same investigators also demonstrated that when LFA-3 or CD48, ligands for CD2 and 2B4, respectively, are coexpressed on target cells with ICAM-1, a ligand for LFA-1, this led to enhanced adhesion of resting NK cells, significantly beyond that observed to target cells expressing only ICAM-1 (38). Furthermore, in the case of LFA-1 expressed on human NK cells, it also can physically associate with DNAM-1, another adhesion and signaling receptor and regulate its phosphorylation state and ability to induce NK cell cytotoxicity (39).…”
Section: Discussionmentioning
confidence: 90%
“…Human NK cells can bind ICAM-1 directly with no direct stimulus, albeit to a much lesser extent for resting human NK cells, therefore it has been proposed that NK cells may be unique (38), and unlike T cells, in not requiring stimulation through an independent activating receptor before LFA-1 can bind tightly to ICAM-1. We did not observe significant binding of resting mouse NK cells or the rat RNK-16 cell to ICAM-1 in the absence of stimulation via an activating receptor.…”
Section: Discussionmentioning
confidence: 99%